Pengaruh Beban Kerja Terhadap Kelelahan Kerja Yang Dimediasi Oleh Konflik Kerja Keluarga (Studi Kasus Pada PT. Astra Internasional Auto 2000 Tenggarong) - Sabran Sabran; Shania Azelia; Nilam Anggar Sari (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This research was conducted at PT. Astra Internasional Auto 2000 Tenggarong Branch. It is a company that has the status as an official dealer of Toyota brand car products located at Jln Pesut RT.035, Timbau Village, Tenggarong District, Kutai Kartanegara Regency. At PT. Astra Internasional Auto 2000 Tenggarong Branch. The purpose is to determine the Effect of Workload, and Work-Family Conflict on Burnout in Employees and the Effect of Workload on Burnout through Work-Family Conflict as a mediation in Employees of PT. Astra Internasional Auto 2000 Tenggarong Branch.The sample used was 33 respondents, namely employees of PT. Astra Internasional Auto 2000 Tenggarong Branch. Data analysis in this study uses the Structural Equation Modeling (SEM) 4 method with the help of Smart-PLS software. The results of analysis showed (1) workload does not affect burnout in employees (2) workload does not affect work-family conflict in employees. (3) work-family conflict affects burnout in employees. (4) workload does not affect burnout through work-family conflict in employees